2006
DOI: 10.1080/09541440500236661
|View full text |Cite
|
Sign up to set email alerts
|

Eye movements during scene inspection: A test of the saliency map hypothesis

Abstract: What attracts attention when we inspect a scene? Two experiments recorded eye movements while viewers inspected pictures of natural office scenes in which two objects of interest were placed. One object had low contour density and uniform colouring (a piece of fruit), relative to another that was visually complex (for example, coffee mugs and commercial packages). In each picture the visually complex object had the highest visual saliency according to the Itti and Koch algorithm. Two experiments modified the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
83
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 109 publications
(90 citation statements)
references
References 26 publications
7
83
0
Order By: Relevance
“…The demands of the task allowed them to focus upon the search for a target, with cognitive override of low-level features either through avoidance of the process of building the saliency map or through disregard of the saliency peaks. This also confirms the result from the search task used by Underwood et al (2006), in which conspicuity was also ineffective in guiding eye movements. The cognitive override of visual saliency is also a feature of Torralba's (2003) model of contextual cueing, in which the visual context becomes available sufficiently early to allow modulation of the saliency map.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…The demands of the task allowed them to focus upon the search for a target, with cognitive override of low-level features either through avoidance of the process of building the saliency map or through disregard of the saliency peaks. This also confirms the result from the search task used by Underwood et al (2006), in which conspicuity was also ineffective in guiding eye movements. The cognitive override of visual saliency is also a feature of Torralba's (2003) model of contextual cueing, in which the visual context becomes available sufficiently early to allow modulation of the saliency map.…”
Section: Discussionsupporting
confidence: 78%
“…This confirms the predictions of models of visual attention that suggest that viewers first determine the regions of low-level variation and build a saliency map that is used to direct the initial eye movements around the scene (Findlay and Walker, 1999;Henderson et al, 1999;Itti and Koch, 2000). It also confirms the results from the memory experiment reported by Underwood et al (2006) in finding a relationship between conspicuity and the early fixation of an object. In Experiment 2 the viewers searched for a small target that was present in half the pictures, and here they were unaffected by conspicuity or congruency.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Given any image, the algorithm computes a so-called saliency map. Saliency maps were tested with success in (Underwood et al, 2006), when the observer task is to memorize images. But it was also shown that when the task is to search for a particular object, this model is no longer valid.…”
Section: The Need For a New Approachmentioning
confidence: 99%